Reaching to sounds in virtual reality: A multisensory-motor approach to promote adaptation to altered auditory cues. (December 2020) - Valzolgher, Chiara; Verdelet, Grègoire; Salemme, Romeo; Lombardi, Luigi; Gaveau, Valerie; Farné, Alessandro; Pavani, Francesco
Abstract: When localising sounds in space the brain relies on internal models that specify the correspondence between the auditory input reaching the ears, initial head-position and coordinates in external space. These models can be updated throughout life, setting the basis for re-learning spatial hearing abilities in adulthood. In addition, strategic behavioural adjustments allow people to quickly adapt to atypical listening situations. Until recently, the potential role of dynamic listening, involving head-movements or reaching to sounds, have remained largely overlooked. Here, we exploited visual virtual reality (VR) and real-time kinematic tracking, to study the role of active multisensory-motor interactions when hearing individuals adapt to altered binaural cues (one ear plugged and muffed). Participants were immersed in a VR scenario showing 17 virtual speakers at ear-level. In each trial, they heard a sound delivered from a real speaker aligned with one of the virtual ones and were instructed to either reach-to-touch the perceived sound source (Reaching group), or read the label associated with the speaker (Naming group). Participants were free to move their heads during the task and received audio-visual feedback on their performance. Most importantly, they performed the task under binaural or monaural listening. Results show that both groups adapted rapidly to monaural listening, improving sound localisation performance across trials and changing their head-movement behaviour. Reaching the sounds induced faster and larger sound localisation improvements, compared to just naming its position. This benefit was linked to progressively wider head-movements to explore auditory space, selectively in the Reaching group. In conclusion, reaching to sounds in an immersive visual VR context proved most effective for adapting to altered binaural listening. Head-movements played an important role in adaptation, pointing to the importance of dynamic listening when implementing training protocols for improving spatial hearing. Highlights: We studied adaptation to monaural listening when listeners interact with sounds. Reaching to sounds reduced errors more than just naming the sound sources. Patterns of spontaneous head-movements changed during adaptation. Exploration of a wider portion of space with the head was functional for adaptation. Reaching to sounds promoted a more effective head-related behaviour.